2020
DOI: 10.47067/ramss.v3i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Organizational Commitment among Academics of HEIs: The Buffering Role of Coworker Support

Abstract: The significance of retaining committed staff is a main focus in contemporary literature in higher education. This study seeks to address issues related to lower employee commitment through a Social Exchange Theory Lens to explore the buffering role of co-worker support on the relationship between Supervisory Support (SS), Organizational Climate (OCL) and commitment HEIs in the Public Sector Pakistan. A quantitative and cross approach to survey was adopted as a survey technique by 366 respondents using a propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The findings of this study aligned with previous researchers who consistently found a significant positive effect of recognition (Giffords, 2009), resources (Aboramadan et al, 2020), training and development (Aboramadan et el., 2020;Ahmad et al, 2017), and the significant negative effect of perceived union support (Asamani & Menash,2013) on affective commitment. Although, the previous researchers have also been agreed on the positive relationship between pay satisfaction and affective commitment (Sariwulan et al, 2019;Scheller & Harrison, 2018), the significant impact of pay satisfaction on affective commitment is not substantiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study aligned with previous researchers who consistently found a significant positive effect of recognition (Giffords, 2009), resources (Aboramadan et al, 2020), training and development (Aboramadan et el., 2020;Ahmad et al, 2017), and the significant negative effect of perceived union support (Asamani & Menash,2013) on affective commitment. Although, the previous researchers have also been agreed on the positive relationship between pay satisfaction and affective commitment (Sariwulan et al, 2019;Scheller & Harrison, 2018), the significant impact of pay satisfaction on affective commitment is not substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…It is a tool to fulfill the goals of organizations through enhancing skills and abilities of their employees (Bashir & long 2015). Studies also suggested that employee development (Ahmad et al, 2017) and training (Aladwan et al, 2015) are significant influencing factors of affective organizational commitment (Johari & Nazir, 2015). In addition, training and development are considered an investment to enhance overall job performance and satisfaction of employees (Aladwan et al, 2015).…”
Section: Training and Developmentmentioning
confidence: 99%
“…Studies show several variables that intervene in the relationship between transformational leadership and organizational performance (Amante, 2018). These include trust in the leader (Sarwar et al, 2015), co-worker support (Ahmad et al, 2017), and organizational learning (Raj & Srivastava, 2016). The mediated transformational leadership behaviors and practices result in changes not only in the behavior of individual employees but also on structures and processes (Friedlander & Brown, 1974as cited in Balci, 2002.…”
Section: Transformational Leadership and Proactive Behaviormentioning
confidence: 99%
“…Similar findings are found in and Krishna (2011), where transformational leaders facilitate the development of team's potential and efficiency to achieve their job performance standard. Furthermore, Ahmad et al (2017) pointed out the massive impact of both transformational leadership and training and development on organisational commitment.…”
Section: Human Governance and Training And Developmentmentioning
confidence: 99%